Health Care Utilization Among Veterans with Pain and Posttraumatic Stress Symptoms. Issue 11 (22nd February 2013) - Outcalt, Samantha D.; Yu, Zhangsheng; Hoen, Helena Maria; Pennington, Tenesha Marie; Krebs, Erin E.
Abstract Objective To examine health care utilization among veterans with both chronic pain and posttraumatic stress symptoms. Methods Retrospective cohort study of 40, 716 veterans in a VA regional network from January 1, 2002 to January 1, 2007. Veterans were categorized into pain‐only, posttraumatic stress disorder symptoms (PTSD)‐only, and pain plus PTSD (pain+PTSD) comparison groups. Negative binomial models were used to compare adjusted rates of primary care, mental health, and specialty pain service use, as well as opioids, benzodiazepines, nonopioid analgesics, and antidepressant prescriptions. Rates of clinic visits were calculated by days per year, and rates of medication use were calculated by prescription months per year. Participants were followed for a mean duration of 47 months. Results Participants were 94.7% men and had a mean age of 58.9 years. Nearly all used primary care (99.2%), 37.1% used pain‐related specialty care, and 33.8% used mental health services. Nonopioid and opioid analgesics were the most commonly used medications (63.7% and 53.8%, respectively). Except for mental health visits, which did not differ between PTSD‐only and pain+PTSD groups, the pain+PTSD group used significantly more of all categories of health care services than the pain‐only and PTSD‐only groups. For example, the pain+PTSD group had 7% more primary care visits (rate ratio [RR] = 1.07; 95% confidence interval [CI]: 1.05, 1.09) than the pain‐only group and 46% more primary care visits than the PTSD‐only group (RR = 1.46; 95% CI: 1.40, 1.52). Adjusted rates of opioid, benzodiazepine, nonopioid analgesic, and antidepressant prescriptions were higher for the pain+PTSD group than either of the comparison groups. Conclusions Our findings support our expectation that veterans with both pain and PTSD symptoms use more health care services than those with pain or PTSD symptoms alone. Research is needed to assess the health care costs associated with increases in health care utilization among these veterans.